Influence of different preparation forms on the loading-bearing capacity of zirconia cantilever FDPs. A laboratory study. Issue 3 (July 2019) - Bishti, Shaza; Jäkel, Carsten; Kern, Matthias; Wolfart, Stefan
Abstract: Purpose: To investigate the impact of inlay design and number of retainer wings on the failure load of all-ceramic resin-bonded inlay-retained cantilever fixed dental prostheses (IRCFDPs) made from a computer-aided design/computer-aided manufacturing (CAD/CAM) yttrium-oxide partially-stabilized zirconia framework(Y-TZP). Methods: Sixty-four extracted human first molars were divided according to preparation design into four groups. Teeth were provided with IRCFDPs representing a premolar pontic and a retainer of variable design: (R1S) shallow inlay/one lingual retainer wing, (R2S) shallow inlay/two retainer wings (lingual/buccal), (R1D) deep inlay/one lingual retainer wing and (R2D) deep inlay/two retainer wings (lingual/buccal). All IRCFDPs were cemented using adhesive resin. Quasi-static fracture strength (QSFS) was tested for 32 specimens after 3 days in a universal testing machine (UTM). The other specimens were stored in a water bath (150 days/37 °C) and thermocycled (37, 500 times, 5–55 °C); then exposed to dynamic loading in a chewing simulator (50 N/1, 200, 000 cycles). Results: The median QSFS (N) for the different designs were: R1S:105.1, R1D:167.5, R2S:147.9, R2D:232.3. The number of retainer wings had a statistically significant influence on the fracture load of both groups, whereas the inlay design had an impact only in the double-retainer wing group. Under dynamic loading, lower failure loads within all groups were reported except for the group R2S. The number of retainer wings continued to significantly influence the failure loads of both groups, whereas no influence of inlay design could be revealed. Conclusions: Double-retainer IRCFDPs showed promising results for replacing single premolars. The inlay design seems to have no significant influence on the fracture strength of these restorations.